ANALISIS PENGARUH TRANSACTION COST TERHADAP HOLDING PERIOD SAHAM BIASA - Eko Budi Santoso (UKDW, 2008)
The main purpose of this study is to test the effect of transaction cost to holding period of common stock. This study investigates whether investors with longer (lower) bid-ask spread as a proxy of transaction cost. Besides, this study also added two independent variables such as market value and variance of return. The statistical method used in this study is two-stage least square regressions because the investor's holding period and the bid-ask spread for each stock are simultaneously ditermined. The result shows that bid ask spread related positively and significant to holding period. The bid ask spread, market value, and variance of return have a significant effect to holding period.